Frequency and predictors of obesity hypoventilation in hospitalized patients at a tertiary health care institution - Yilmaz Bülbül (Annals of Thoracic Medicine, 2014)
Objectives: Patients with obesity hypoventilation syndrome (OHS) have significant morbidity and mortality. Early diagnosis and treatment is important and there are limited data on its prevalence and predictive factors. The objective of this observational study was to determine the frequency and predictors of OHS in hospitalized patients at a tertiary health care institution. Materials and Methods: All blood gas analyses of hospitalized adult (age over 18 years) patients were prospectively recruited from the biochemistry laboratory at a tertiary health care center between August 2009 and July 2010. Patients who had hypercapnia (PaCO 2 ≥ 45 mmHg) while breathing room air were included and clinical and laboratory data were obtained from hospital records. A standard questionnaire was also filled by face-to-face interview with patients and/or relatives. Results: A total of 9480 patients′ arterial blood gases were evaluated and 330 patients (3.4%) who met the selection criteria were included in the analysis during the study period. Hypoventilation was associated with acute diseases in 64.2% and chronic diseases in 35.8% of the patients. Of the chronic hypoventilation patients, 24.4% had OHS. Univariate logistic regression analysis showed that, female gender, body mass index (BMI), smoking, PaO 2 , SaO 2 and a PaCO 2 /BMI <1.5 were significantly related to OHS. In multivariate logistic regression analysis, BMI >35 kg/m 2 , SaO 2 <91.4% and PaCO 2 /BMI <1.5 were significantly related to OHS. A PaCO 2 /BMI <1.5 was an independent variable strongly predictive of OHS (odds ratio: 36.9, 95% of the confidence interval: 2.75-492.95, P = 0.007). Conclusions: OHS is a common cause of chronic alveolar hypoventilation. A careful examination PaCO 2 /BMI ratio may prevent misdiagnoses among hypercapnic patients.